A biodegradable resin composite material and its application in automobile exterior parts

By melt blending carboxy functionalized polylactic acid with carbon fiber and modifier materials, a degradable resin composite material with excellent heat resistance, degradability and mechanical properties is obtained, which solves the problems of insufficient strength, easy aging, and flammable polylactic acid materials in automotive exterior parts applications, and achieves high mechanical properties and good environmental protection properties of the material.

CN119775740APending Publication Date: 2025-04-08ANHUI PEILI NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411960348.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing biodegradable polylactic acid materials have problems such as insufficient strength, easy aging, and flammable in the application of automotive exterior parts, which limits their wide application in automotive exterior parts.

Method used

By stirring and mixing carboxylic functionalized polylactic acid, carbon fiber, modifier, catalyst and processing aid in a mixer, and adding it to a twin-screw extruder to melt blend, a degradable resin composite material with excellent heat resistance, degradability and mechanical properties is obtained, and a series of chemical reactions are produced to improve the material's ultraviolet resistance and flame retardant properties.

Benefits of technology

It realizes the high mechanical properties, good heat resistance and degradability of the material, and at the same time improves the resistance to ultraviolet and flame retardant properties, solves the aging and combustion problems of polylactic acid materials in the application of automotive exterior parts, and has important application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005216944470000031
    Figure BDA0005216944470000031
  • Figure BDA0005216944470000041
    Figure BDA0005216944470000041
  • Figure BDA0005216944470000042
    Figure BDA0005216944470000042
Patent Text Reader

Abstract

The invention discloses a degradable resin composite material and its application in automobile exterior parts, belonging to the technical field of degradable materials. The invention comprises the following raw materials in parts by weight: 90-100 parts of carboxyl functionalized polylactic acid, 10-16 parts of carbon fiber, 5-15 parts of modifier, 0.5-1.5 parts of catalyst, and 4-8 parts of processing aid. The polylactic acid and carbon fiber are made into a composite material, which gives the material excellent heat resistance, degradability and mechanical properties; wherein, the modifier molecule contains various functional groups, which can improve the material's anti-ultraviolet and flame retardant properties, and the performance is long-term and stable, and not easy to fall off; therefore, the composite material prepared by the invention has high mechanical properties, good heat resistance, stable and efficient anti-ultraviolet and flame retardant properties, and is environmentally friendly and degradable, and has important application value in the technical field of automobile exterior parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of degradable materials, and in particular, relates to a degradable resin composite material and its application in automobile exterior trims. Background Art

[0002] In recent years, with the rapid development of the automobile industry, automobile exterior parts have also received more and more attention. Automobile exterior parts refer to parts installed on the outside of the car for decoration, protection and improvement of automobile performance. Automobile exterior parts include front and rear bumpers, wheel arches, air intake grilles, headlights, wheels and rear wings. The main materials of automobile exterior parts are plastic, metal, fiberglass, etc. Among them, plastic exterior parts have the advantages of light weight, corrosion resistance, and easy processing, and are widely used in the field of automobile exterior parts. However, when the car is abandoned, these plastic exterior parts are difficult to decompose and will become pollutants, which are very harmful to the environment. Therefore, people are now paying more and more attention to the development of environmentally friendly and degradable materials.

[0003] Degradable materials refer to materials that can be degraded into small molecules such as carbon dioxide and water by microorganisms or natural factors under natural environmental conditions, such as soil, water environment, light, etc., or under specific conditions such as composting or anaerobic digestion. These materials are regarded as an important solution to plastic pollution due to their environmentally friendly characteristics. The use of degradable materials in the application of automotive exterior parts is gradually increasing. Among them, polylactic acid is a bio-based degradable plastic with good biocompatibility and heat resistance. It has been used in the automotive industry to manufacture parts such as air intake grilles and triangular window frames, and has great development prospects. However, the strength of polylactic acid is not as good as that of ordinary plastics, and the application of polylactic acid in automotive exterior parts is easily exposed to sunlight for a long time outdoors, which can easily cause the material to age and turn yellow; finally, polylactic acid is a polymer material with a low oxygen index. It is easy to burn in the event of a car accident, and there are certain safety hazards. These shortcomings limit the application of polylactic acid in automotive exterior parts. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of degradable material technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a degradable resin composite material and its application in automobile exterior parts.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A biodegradable resin composite material is prepared by the following steps:

[0007] Carboxyl functionalized polylactic acid (PLA-COOH), carbon fiber, modifier, catalyst and processing aid are stirred and mixed in a mixer for 10-20 minutes, and then added into a twin-screw extruder for melt blending and extrusion to obtain a biodegradable resin composite material.

[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 90-100 parts of carboxyl functionalized polylactic acid, 10-16 parts of carbon fiber, 5-15 parts of modifier, 0.5-1.5 parts of catalyst, and 4-8 parts of processing aid.

[0009] Furthermore, the catalyst is one of stannous chloride and stannous oxide.

[0010] Furthermore, the processing aid is one of olive oil, beeswax and zinc stearate.

[0011] With polylactic acid as the matrix, the material has good heat resistance and biodegradability; adding carbon fiber can further enhance the heat resistance of the material and also improve the mechanical properties of the material.

[0012] Furthermore, the modifier is prepared by the following steps:

[0013] S1. Add cyanuric chloride and acetone to a three-necked flask, stir for 15 min in an ice bath at 5°C, then dissolve 2,4-dihydroxybenzophenone and sodium hydroxide in acetone and distilled water respectively, stir and mix well, then add them to the three-necked flask in turn, react at 50°C for 4 h, the reaction is completed, filter, wash the filter residue with distilled water and ethanol in turn 2-3 times, put it in an oven for drying, and then separate and purify it by column chromatography (the eluent is a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two is 5:1), and remove the eluent by rotary evaporation to obtain intermediate 1; the ratio of cyanuric chloride, acetone, 2,4-dihydroxybenzophenone, sodium hydroxide, and distilled water is 19.1 g:120 mL:42.8 g:8.3 g:50 mL;

[0014] Sodium hydroxide can react with the hydroxyl group in the 2,4-dihydroxybenzophenone molecule. However, since the hydroxyl group at the ortho position of 2,4-dihydroxybenzophenone forms a hydrogen bond with the carbonyl group and is not easily broken, sodium hydroxide reacts with the hydroxyl group at the para position to form sodium phenolate with stronger nucleophilicity. Sodium phenolate, as a nucleophilic reagent, attacks the carbon atom connected to the chlorine atom on cyanuric chloride, so that the chlorine atom is replaced, thereby generating an ether bond. By controlling the molar ratio of 2,4-dihydroxybenzophenone to cyanuric chloride to be close to 2:1 and the cyanuric chloride to be slightly excessive, only two chlorine groups on the cyanuric chloride participate in the reaction, and intermediate 1 is obtained. The specific reaction process is shown below:

[0015]

[0016] S2. In a three-necked flask equipped with a stirring device, the intermediate 1, 4-hydroxystyrene and N,N-dimethylformamide (DMF) are mixed, and then sodium hydroxide is dissolved in distilled water, stirred evenly, and then added to the three-necked flask. After stirring, the reaction temperature is controlled to 60°C, and the reaction is kept warm for 5 hours. After the reaction is completed, the solvent is removed by rotary evaporation, and the mixture is placed in an oven for drying. Then, the mixture is separated and purified by column chromatography (the eluent is a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two is 7:1), and the eluent is removed by rotary evaporation to obtain intermediate 2; the ratio of the amount of intermediate 1, 4-hydroxystyrene, N,N-dimethylformamide, sodium hydroxide, and distilled water is 53.9 g:11.9 g:100 mL:4.1 g:50 mL;

[0017] Under the catalysis of sodium hydroxide, intermediate 1 reacts with 4-hydroxystyrene to obtain intermediate 2. The principle is the same as step S1. The specific reaction process is as follows:

[0018]

[0019] S3. In a three-necked flask, the intermediate 2, azobisisobutyronitrile (AIBN) and N,N-dimethylformamide were stirred and mixed uniformly, and then 6-mercaptohexanol was added dropwise. The mixture was stirred continuously during the addition process. After the addition was completed, the temperature of the system was maintained at 75°C and the reaction was kept warm for 6 hours. After the reaction was completed, the mixture was filtered, the solvent was removed by distillation under reduced pressure, and the mixture was dried in vacuo to obtain a modifier; the ratio of the amount of the intermediate 2, azobisisobutyronitrile, N,N-dimethylformamide and 6-mercaptohexanol was 62.4 g:0.2 g:200 mL:13.4 g;

[0020] Under the action of AIBN, the unsaturated carbon-carbon double bond on the intermediate 2 undergoes a thiol-ene click reaction with the thiol group on 6-mercaptohexanol to obtain a modifier; the structure of the modifier is shown below:

[0021]

[0022] The prepared modifier molecule contains two symmetrical benzophenone groups. As a type of ultraviolet absorber, benzophenone can consume the ultraviolet radiation energy absorbed by the matrix through keto-enol tautomerism, greatly improving the anti-ultraviolet performance of the matrix. In addition, the modifier molecule also contains sulfur, triazine structure and hydroxyl group. The introduced sulfur element can accelerate the isomerization of the matrix to produce a large amount of CO2 and catalyze the progress of the Fries rearrangement of the matrix to promote carbonization, which can improve the flame retardant performance of the matrix. As a nitrogen-based flame retardant, the triazine structure will produce nitrogen-containing gas during combustion, dilute and reduce the smoke density, and self-condense at high temperature to form melem to make the carbon layer tight, which can synergize with sulfur element and significantly enhance the flame retardant performance of the matrix. Finally, the hydroxyl group contained at one end of the modifier molecule can produce chemical bonding with carboxyl functionalized polylactic acid under the action of a catalyst, thereby enhancing the interaction force between the modifier molecule and the matrix, making it difficult for the small molecule modifier to migrate and seep out, and ensuring the long-term stability of the modifier performance.

[0023] Beneficial effects of the present invention:

[0024] 1. The present invention makes a composite material of polylactic acid and carbon fiber, thereby giving the material excellent heat resistance, degradability and mechanical properties;

[0025] 2. Through a series of chemical reactions, a modifier is obtained. The modifier molecules contain various functional groups, which can improve the UV resistance and flame retardancy of the material, and the performance is long-lasting and stable and not easy to fall off;

[0026] Therefore, the composite material prepared by the present invention has high mechanical properties, good heat resistance, stable and efficient anti-ultraviolet and flame retardant properties, and is environmentally friendly and degradable, and has important application value in the field of automobile exterior parts technology. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1

[0029] Preparation of modifier:

[0030] S1, add 19.1g cyanuric chloride and 40mL acetone to a three-necked flask, stir for 15min under ice bath condition at 5℃, then dissolve 42.8g 2,4-dihydroxybenzophenone and 8.3g sodium hydroxide in 80mL acetone and 50mL distilled water respectively, stir and mix evenly, add them to the three-necked flask in sequence, react at 50℃ for 4h, the reaction is completed, filter, wash the filter residue with distilled water and ethanol in sequence 2-3 times, put it in an oven for drying, and then separate and purify it by column chromatography (the eluent is a mixed solvent of petroleum ether / ethyl acetate, the volume ratio of the two is 5:1), and remove the eluent by rotary evaporation to obtain intermediate 1;

[0031] S2, in a three-necked flask equipped with a stirring device, 53.9g of intermediate 1, 11.9g of 4-hydroxystyrene and 100mL of N,N-dimethylformamide were mixed, and 4.1g of sodium hydroxide was dissolved in 50mL of distilled water, stirred evenly, and added to the three-necked flask. After stirring, the reaction temperature was controlled to 60°C, and the reaction was kept warm for 5h. After the reaction was completed, the solvent was removed by rotary evaporation, and the mixture was placed in an oven for drying. Then, the mixture was separated and purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 7:1), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0032] S3. In a three-necked flask, add 62.4 g of intermediate 2, 0.2 g of azobisisobutyronitrile and 200 mL of N,N-dimethylformamide, stir and mix evenly, then drop 13.4 g of 6-mercaptohexanol, stirring continuously during the addition process. After the addition is completed, maintain the temperature of the system at 75°C and keep the reaction warm for 6 hours. After the reaction is completed, filter, remove the solvent by distillation under reduced pressure, and vacuum dry to obtain a modifier.

[0033] Embodiment 2

[0034] Preparation of modifier:

[0035] S1, add 38.2g cyanuric chloride and 80mL acetone to a three-necked flask, stir for 15min under ice bath condition at 5°C, then dissolve 85.6g 2,4-dihydroxybenzophenone and 16.6g sodium hydroxide in 160mL acetone and 100mL distilled water respectively, stir and mix evenly, then add them to the three-necked flask in sequence, react at 50°C for 4h, the reaction is completed, filter, wash the filter residue with distilled water and ethanol twice in sequence, put it in an oven for drying, and then separate and purify it by column chromatography (the eluent is a mixed solvent of petroleum ether / ethyl acetate, the volume ratio of the two is 5:1), and remove the eluent by rotary evaporation to obtain intermediate 1;

[0036] S2, in a three-necked flask equipped with a stirring device, 107.8g of intermediate 1, 23.8g of 4-hydroxystyrene and 200mL of N, N-dimethylformamide were mixed, and 8.2g of sodium hydroxide was dissolved in 100mL of distilled water, stirred evenly, and added to the three-necked flask. After stirring, the reaction temperature was controlled to 60°C, and the reaction was kept warm for 5h. After the reaction was completed, the solvent was removed by rotary evaporation, and the mixture was placed in an oven for drying. Then, the mixture was separated and purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 7:1), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0037] S3. In a three-necked flask, stir and mix 124.8 g of intermediate 2, 0.4 g of azobisisobutyronitrile and 400 mL of N,N-dimethylformamide, and then drop 26.8 g of 6-mercaptohexanol. Stir continuously during the addition process. After the addition is completed, maintain the temperature of the system at 75°C and keep the reaction for 6 hours. After the reaction is completed, filter, remove the solvent by distillation under reduced pressure, and vacuum dry to obtain a modifier.

[0038] Embodiment 3

[0039] 90 g of carboxyl functionalized polylactic acid, 10 g of carbon fiber, 5 g of the modifier prepared in Example 1, 0.5 g of stannous chloride and 4 g of olive oil were stirred and mixed in a mixer for 10 minutes, and then added to a twin-screw extruder, melt-blended and extruded to obtain a biodegradable resin composite material.

[0040] Embodiment 4

[0041] 95 g of carboxyl functionalized polylactic acid, 13 g of carbon fiber, 10 g of the modifier prepared in Example 2, 1 g of stannous oxide and 6 g of beeswax were stirred and mixed in a mixer for 15 minutes, and then added to a twin-screw extruder, melt-blended and extruded to obtain a biodegradable resin composite material.

[0042] Embodiment 5

[0043] 100 g of carboxyl functionalized polylactic acid, 16 g of carbon fiber, 15 g of the modifier prepared in Example 2, 1.5 g of stannous oxide and 8 g of zinc stearate were stirred and mixed in a mixer for 20 minutes, and then added to a twin-screw extruder, melt-blended and extruded to obtain a biodegradable resin composite material.

[0044] Comparative Example 1

[0045] The modifier in Example 5 was replaced by a commercially available anti-ultraviolet additive, and the remaining steps were the same as those in Example 5.

[0046] Comparative Example 2

[0047] A commercially available flame retardant was used to replace the modifier in Example 5, and the remaining steps were the same as those in Example 5.

[0048] Embodiments 3, 4, 5, and comparative examples 1 and 2 were made into corresponding shapes according to different test standards, and the following performance tests were performed:

[0049] The biodegradation rates of Examples 3, 4 and 5 were determined using the national standard GB / T 19811-2005;

[0050] The tensile properties are determined using the national standard GB / T 1040.2-2006 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics";

[0051] The sample was placed in a xenon lamp aging test chamber for accelerated aging for 30 days. The aging conditions were air atmosphere, xenon lamp wavelength 280-800nm, and irradiation intensity 550W / m 2 , test the tensile strength of the sample before and after aging (GB / T 1040.2-2006) and calculate the retention rate of tensile strength; retention rate of tensile strength = tensile strength after test / tensile strength before test × 100%;

[0052] The national standard GB / T 8924-2005 "Fiber reinforced plastic combustion performance test method oxygen index method" was used to measure the limiting oxygen index of Examples 3, 4, 5 and Comparative Example 2 before and after standing at room temperature for 200 days;

[0053] The measured results are shown in the following table:

[0054]

[0055] It can be seen from the above table that compared with the comparative example, the added modifier in the embodiment of the present invention can effectively enhance the anti-ultraviolet and flame retardant properties of the material, and has little effect on the mechanical properties of the material. The performance is long-term stable, environmentally friendly and degradable, and has important application value in the field of automotive exterior parts technology.

[0056] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0057] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A degradable resin composite material, characterized in that: Prepared by the following steps: The carboxyl functionalized polylactic acid, carbon fiber, modifier, catalyst and processing aid are stirred and mixed in a mixer, and then added into a twin-screw extruder, melt-blended and extruded to obtain a biodegradable resin composite material.

2. A degradable resin composite material according to claim 1, characterized in that: The modifying agent is prepared by the following steps: S1. Add cyanuric chloride and acetone to a three-necked flask, stir for 15 min in an ice bath at 5°C, then dissolve 2,4-dihydroxybenzophenone and sodium hydroxide in acetone and distilled water respectively, stir and mix well, then add them to the three-necked flask in sequence, react at 50°C for 4 h, and after the reaction is completed, filter, wash the filter residue, dry, separate and purify by column chromatography, and rotary evaporate to obtain intermediate 1; S2, mixing the intermediate 1, 4-hydroxystyrene and N,N-dimethylformamide, dissolving sodium hydroxide in distilled water, stirring evenly, adding the mixture into a three-necked flask, stirring, reacting at 60° C. for 5 h, and after the reaction is complete, rotary evaporation, drying, column chromatography separation and purification, and rotary evaporation to obtain the intermediate 2; S3. Stir and mix the intermediate 2, azobisisobutyronitrile and N,N-dimethylformamide evenly, then drop 6-mercaptohexanol while stirring continuously. After the dropwise addition is completed, heat and react at 75°C for 6 hours. After the reaction is completed, filter, distill under reduced pressure, and dry in vacuo to obtain a modifier.

3. A degradable resin composite material according to claim 2, characterized in that: In step S1, the ratio of cyanuric chloride, acetone, 2,4-dihydroxybenzophenone, sodium hydroxide and distilled water is 19.1 g: 120 mL: 42.8 g: 8.3 g: 50 mL.

4. A degradable resin composite material according to claim 2, characterized in that: In step S2, the ratio of the amount of intermediate 1, 4-hydroxystyrene, N,N-dimethylformamide, sodium hydroxide and distilled water is 53.9 g:11.9 g:100 mL:4.1 g:50 mL.

5. The biodegradable resin composite material according to claim 2, characterized in that: In step S3, the ratio of the amount of intermediate 2, azobisisobutyronitrile, N,N-dimethylformamide, and 6-mercaptohexanol is 62.4 g: 0.2 g: 200 mL: 13.4 g.

6. The biodegradable resin composite material according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 90-100 parts of carboxyl functionalized polylactic acid, 10-16 parts of carbon fiber, 5-15 parts of modifier, 0.5-1.5 parts of catalyst, and 4-8 parts of processing aid.

7. The biodegradable resin composite material according to claim 1, characterized in that: The catalyst is one of stannous chloride and stannous oxide.

8. The biodegradable resin composite material according to claim 1, characterized in that: The processing aid is one of olive oil, beeswax and zinc stearate.

9. Use of the degradable resin composite material according to claim 1 in the field of automobile exterior parts.